The artistic series El Siglo: Between fragmentary rewriting or collage of disaffected remnants of the past disaffected from the past and memory technique (Mayéutica Revista Científica de Humanidades y Artes, 2025)
The author analyzes the work El Siglo (20212023) presented in the collective art exhibition Ecolocalidades, inaugurated at the Centro de Investigación de la Fotografía (CIF) at the Universidad de las Artes de Guayaquil, in August 2023. This exhibition was part of the international meeting Locality and technodiversity. Towards artistically and ecologically smart territories, whose activities were produced by the research project NEST (Network Ecologically Smart Territories), and brought together the work of several artists from Ecuador and Latin America. The author develops her analysis by focusing on certain notions that guide the activities carried out by the NEST project, as well as on the idea developed by Bernard Stiegler that the history of memory is specifically a history of the conservation of memory techniques that function in a present different from the one to which they belong. Additionally, the author draws on the curatorial concepts of the exhibition Memories of the Future. Libraries and technologies launched in 1987 by the French philosopher, to expand on the ideas of fragmentary rewriting or collage of disaffected remnants of the past and of memory technique, present in the work El Siglo.Translated with DeepL.com (free version)
Keywords: El Siglo; Memories of the Future; Bernard Stiegler; Contemporary art of Ecuador; Historical archives of Ecuador